Finally Fit for Purpose: The Evolution of Australian Prison Architecture. (June 2015) - Grant, Elizabeth; Jewkes, Yvonne
This article argues that Australian prisons have uncritically emulated American penitentiaries in their architecture and structure. We suggest that simply transporting physical design models from one geographic and politico-cultural setting to another, with little commitment to understanding the context-bound philosophies and conditions that underpin such models, has been highly problematic. The result has been an Australian penal estate that for decades was incompatible with its aims and purpose. Finally, we discuss the eventual introduction of unique, innovative styles of penal architecture in Australia, which are not only appropriate to their culture and context, but represent world-class developments in penal design.